2001
DOI: 10.1159/000054763
|View full text |Cite
|
Sign up to set email alerts
|

Prehospital and In-Hospital Delays in Acute Stroke Care

Abstract: Current guidelines emphasize the need for early stroke care. However, significant delays occur during both the prehospital and in-hospital phases of care, making many patients ineligible for stroke therapies. The purpose of this study was to systematically review and summarize the existing scientific literature reporting prehospital and in-hospital stroke delay times in order to assist future delivery of effective interventions to reduce delay time and to raise several key issues which future studies should co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
142
0
9

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(159 citation statements)
references
References 55 publications
5
142
0
9
Order By: Relevance
“…Although several studies have reported on means of improving the timeliness of thrombolysis in acute stroke, [14][15][16][17][18]25 none has specifically focused on public safety net hospitals, which generally have less funding and treat more underor uninsured patients. As one of these hospitals, our institution treats a diverse and relatively socioeconomically disadvantaged population.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although several studies have reported on means of improving the timeliness of thrombolysis in acute stroke, [14][15][16][17][18]25 none has specifically focused on public safety net hospitals, which generally have less funding and treat more underor uninsured patients. As one of these hospitals, our institution treats a diverse and relatively socioeconomically disadvantaged population.…”
Section: Discussionmentioning
confidence: 99%
“…12,13 Despite the clear benefits of early thrombolysis, delays in stroke recognition, hospital arrival, emergency department (ED) triage, imaging, neurology consultation, and treatment preparation and delivery impede the achievement of recommended door-to-needle (DTN) times of less than 60 minutes. 14,15 Accordingly, there exists substantial interest in targeted, effective interventions to reduce these times. Numerous studies have examined various targeted interventions to this end, including a systematic quality improvement study conducted as part of the original National Institutes of Neurologic Disorders and Stroke-sponsored trial showing benefit with tPA.…”
Section: Introductionmentioning
confidence: 99%
“…However, the excitotoxic phase mediated by the release of excitatory acids into the brain peaks within 1 to 2 h after ischemia, and treatments with anti-excitotoxic drugs are only effective when given within 1 to 2 h after focal ischemia in animal models [80] . Considering that the median hospital arrival time for stroke patients is 3 to 6 h [81] and all of the trials of antiexcitotoxic drugs have been used to treat patients up to at least 6 h after the onset of symptoms, the negative outcomes of the 35 completed trials of antiexcitotoxic agents are not surprising. In the development of new therapies, focus must be placed on targets producing long-lasting protection and efficacy even when treatments are given during or at the 4 to 6 h after symptom onset, which is when patients generally arrive at the hospital.…”
Section: Discussionmentioning
confidence: 99%
“…(35) ' nın İtalya'da yaptıkları 189 hastalık çalışmada hastaların %31'inin ilk 2 saat içinde başvurdukları görülmektedir. Akut inme tedavisinin başlamasındaki gecikme değişik aşamalarda gelişmektedir fakat en büyük zaman dilimi hastane dışında yitirilmektedir (36) . Ferro ve ark.…”
Section: Materyal Metodunclassified